2004
DOI: 10.1002/lt.20254
|View full text |Cite
|
Sign up to set email alerts
|

Graft and patient survival after adult live donor liver transplantation compared to a matched cohort who received a deceased donor transplantation

Abstract: Live donor liver transplantation (LDLT) has become increasingly common in the United States and around the world. In this study, we compared the outcome of 764 patients who received LDLT in the United States and compared the results with a matched population that received deceased donor transplantation (DDLT) using the United Network for Organ Sharing (UNOS) database. For each LDLT recipient (n ‫؍‬ 764), two DDLT recipients (n ‫؍‬ 1,470), matched for age, gender, race, diagnosis, and year of transplantation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
98
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 15 publications
(14 reference statements)
1
98
3
Order By: Relevance
“…HBV infection was found in 89.3% (n 5 293) of recipients. The median Child-Pugh score was 6 (interquartile range [IQR], [4][5][6][7][8], and the median MELD score was 11 (IQR, 9-16). With regard to T stage, T2 was the most common, observed in 58.2% (n 5 191) of the patients, followed by T1 in 23.5% (n 5 77) of the patients.…”
Section: Baseline Characteristics Of the Propensity-matched Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…HBV infection was found in 89.3% (n 5 293) of recipients. The median Child-Pugh score was 6 (interquartile range [IQR], [4][5][6][7][8], and the median MELD score was 11 (IQR, 9-16). With regard to T stage, T2 was the most common, observed in 58.2% (n 5 191) of the patients, followed by T1 in 23.5% (n 5 77) of the patients.…”
Section: Baseline Characteristics Of the Propensity-matched Groupsmentioning
confidence: 99%
“…Shear stress caused by transient portal hypertension can cause acute mechanical injury, which then induces severe inflammatory responses to negatively affect the outcomes of liver transplantation (LT). (4)(5)(6) Reports showed that SFSG causes graft dysfunction following LT and adversely affects graft survival despite rapid hepatic regeneration. (4)(5)(6) Moreover, studies have reported an association between SFSG and high tumor recurrence rates following LT for hepatocellular carcinoma (HCC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Innovative ways of expanding the donor pool are the use of split and live donor liver transplantation as well as the use of liver allografts containing appreciable steatosis or with past exposure to hepatitis B. [4][5][6] The use of HCV-positive (HCVϩ) allografts/grafts in HCV patients is another such strategy and has now become routine at most transplant centers.…”
mentioning
confidence: 99%
“…[4][5][6] Similarly, the presence of significant steatosis in the graft and a long cold ischemia time are also associated with a poor outcome of HCV infection after LT. 3 Recently, several reports have suggested that recurrence of HCV infection is more severe in patients undergoing living donor liver transplantation (LDLT) compared to deceased donor liver transplantation (DDLT). 1,7 This observation is still highly controversial, as data from other studies have found similar patient and graft survival rates in both groups of patients. 8,9 The topic is extremely relevant, as LDLT has become an important strategy to expand the organ donor pool.…”
Section: R Ecurrence Of Hepatitis C Virus (Hcv) Infectionmentioning
confidence: 96%